GENDER AND AGE FEATURES OF NON-MOTOR MANIFESTATIONS OF PARKINSON'S DISEASE - Геник, С. І.; Гриб, В. А.; Дорошенко, О. О.; Максимчук, Л. Т.; Васильківська, Л. Я.; Геник, Я. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article contains the results of the study of Parkinson's disease non-motor manifestations severity based on age and sex of the patient and stage of the disease. It was revealed the prevalence of the disease in elderly men. Non-motor signs manifested the most significantly in senile age women and their severity increased with the progression of Parkinson's disease motor manifestations.